PRESENTASASI ADZAN DENGAN SUARA MELIUK-LIUK DALAM PERSPEKTIF FIQIH - Multazim A.A (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2017)
Adzan is taka sing again among Muslims, echoed every prayer time for childbirth rituals of Islam and a notice of the entry of the prayer time, as well as invite Muslims to praying obligatory prayers in congregation, where the presentation is very fariatif, with loud noises and tartil recitation in accordance with, and there are too loud, too long and meliyuk-liyuk as the majority of the public do well in urban areas, even in different diperdesaan remote corners of the country. Presentation (practice) appearance, with a sound Adzan meliyuk-liyuk mengiramakan by adding letters or harokat or mad/long, thicken your readings the sentence, memfasikh-fasikh right and too long, as has become the tradition/habit society, law makruh can even be unlawful when changing the meaning and raises doubts.